IT Revolutionizing the Supply chain Transformation: A Case Study of Unilever Pakistan Ltd. - Muhammad Jiyad Shaikh (International Journal of Supply Chain Management, 2013)
Supply chain Management is a combination of three words supply, chain and management. Supply is all about meeting the needs, wants and demands of customers where as the chain actually represents connectivity. Further management is all about planning the supplies transit to meet demand , organizing the processes sequence for it , controlling and ensuring the process quality through check points and gate control systems, leading by defining process ownership and staffing by right sizing at each and every step. Thus aforementioned three words combined together to form supply chain management. Supply chain management is also to provide the best possible services to the customer with maximum cost effectiveness. Another recent development in the field of supply chain management is the evolution of supply chain operation reference model also known as SCOR model. This model was first introduced by the supply chain council (SCC), a globally known corporation due to excellence in supply chain practices and systems formulation. This SCOR model is actually a reference model standardized terminology and processes [42] which actually emphasizes on benchmarking. This benchmarking is actually related to an operational measurement in order to craft a portfolio for improvement which is directly linked and tied with balance sheet of the company for improved performance along with bottom line increment. Information technology (IT) applications in the field of supply chain management (SCM) has achieved a significance by virtue of its capability and ability to lessen the costs and enhanced responsiveness in the supply chain functions [41], [15] , [19], [36], [45], [43].